The attitudes of teachers and 11th form students towards the application of podcasts to listening lessons at Dong Quan high school = thái độ của giáo viên và học sinh lớp 11 với việc áp dụng podcasts trong các tiết học nghe ở trường trung học phổ thông Đồng Quan - Nguyễn, Thị Bích Thập (2020)
The enhancement of listening skills has drawn much attention in the teaching and learning process and podcasts have been applied at Dong Quan high school for the improvement. This research is carried out to find out techniques employed by teachers to help students learn listening with podcasts. At the same time, the research is aimed at investigating the attitudes of teachers and 11th form students at Dong Quan high school towards the application of podcasts to their listening lessons. To reach the research aims, survey questionnaires were administered to teachers and students and semi-structured interviews were designed and carried out with four teachers. Participants were 10 English teachers and 120 students of grade 11 at Dong Quan high school. Findings show that various techniques were fully employed to help students learn listening with podcasts. Secondly, most of teachers and students agreed that podcasts were extremely helpful to improve listening skills. Thirdly, teachers used podcasts with low frequency because designing a lesson plan with podcasts required a great deal of time and effort. Moreover, it was the lack of training in designing listening tasks and the variety of students’ levels that limited the use of podcasts to teaching listening comprehension. Based on the findings of the research, more techniques would be suggested in the study in order to improve the quality of listening lessons with podcasts.